Spiropyran-Based Fluorescent Anion Probe and Its Application for Urinary Pyrophosphate Detection - Shao, Na; Wang, Hao; Gao, XiaDi; Yang, RongHua; Chan, WingHong (Analytical chemistry (Washington), 2010)
In recent decades, numerous spiropyran derivatives have been designed and utilized for optical sensing of metal ions. However, there is still less research on spiropyran-based anion sensors. In this work, a new spiropyran compound (L) appended with a pendant bis(2-pyridylmethyl)amine was synthesized and used in fluorescent sensing of pyrophosphate ion (PPi) in aqueous solution. The molecular recognition and signal transduction are based on the cooperative ligation interactions and the ligation-induced structural conversion of the spiropyran, which leads to a significant change in the photophysical property of the spiropyran. In an ethanol/water solution (30:70, v/v) at pH 7.4, ligation of L with Zn2+ causes an intense fluorescence emission at 620 nm at the expense of the original fluorescence at 560 nm. Once PPi was introduced, interaction between PPi and the L−Zn2+ complex leads to full quenching of the 620 nm band emission which was concomitant with recovery of the 560 nm band emission, and the fluorescence intensity ratio, F 560/F 620, is proportional to the PPi concentration. Under the optimum condition, the L−Zn2+ complex responds to PPi over a dynamic range of 1.0 × 10−6 to 5.0 × 10−4 M, with a detection limit of 4.0 × 10−7 M. The fluorescence response is highly selective for PPi over other biologically related substrates, especially the structurally similar anions, such as phosphate and adenosine triphosphate. The mechanism of interaction among L, Zn2+, and PPi was primarily studied by 1H NMR, 31P NMR, and HRMS. To demonstrate the analytical application of this approach, the PPi concentration in human urine was determined. It was on the order of 3.18 × 10−5 M, and the mean value for urinary PPi excretion by three healthy subjects was 62.4 μmol/24 h.